2022
DOI: 10.15304/rips.21.2.8233
|View full text |Cite
|
Sign up to set email alerts
|

Migración internacional de retiro y urnas: elecciones municipales españolas de 2019

Abstract: El fenómeno gerontomigratorio es una realidad nacional cuya concreción demográfica a nivel local puede incidir en los resultados de los comicios en los que tienen derecho de sufragio. Este artículo aborda el compromiso cívico de los gerontoinmigrantes de retiro y analiza los factores (des)movilizadores de su voto, siendo las últimas elecciones municipales celebradas en España, de 2019, el caso de estudio. Aparte de los correspondientes datos facilitados por el Instituto Nacional de Estadística y por el Ministe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The measure was originally developed by Solé‐Ollé and Viladecans‐Marsal (2012) to quantify “influence [over city officials] wielded by land developer lobbies” (10). Bribes in exchange for adjustments to land regulations are the most common type of local corruption in Spain (e.g., Fundación Alternativas 2007; Darias, Martín, and González 2012; Sánchez 2007). This variable unobtrusively captures the phenomenon by measuring the change in land supply for urban development between two elections.…”
Section: Methodsmentioning
confidence: 99%
“…The measure was originally developed by Solé‐Ollé and Viladecans‐Marsal (2012) to quantify “influence [over city officials] wielded by land developer lobbies” (10). Bribes in exchange for adjustments to land regulations are the most common type of local corruption in Spain (e.g., Fundación Alternativas 2007; Darias, Martín, and González 2012; Sánchez 2007). This variable unobtrusively captures the phenomenon by measuring the change in land supply for urban development between two elections.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, studies of this kind corroborate the lower interest shown towards local electoral processes, owing to the limited number of studies carried out to date in contrast with other fields. Along these lines, part of such content has been approached as a group of various cases within one single election (Borja-Orozco 2022; Criado et al 2013;Hagar 2015;Jara et al 2017;Kropf 2021;Lampoltshammer et al 2023;López-de-Ayala-López et al 2016;Martínez-Rolán 2016;˙Ikiz et al 2014;Sobaci et al 2016). On the other hand, others have tended to focus on one specific local campaign or election as a case study (Carrillo-Rodríguez and Toca-Torres 2022;García-Carretero and Pérez-Altable 2017;Lombana-Bermúdez et al 2022;Nicasio-Varea and Pérez-Galdón 2021;Raynauld and Greenberg 2014) 3 .…”
Section: Theoretical Foundations and Backgroundmentioning
confidence: 99%